The Role of Knowledge of the International Marketing Environment In Choosing the FDI Strategy for Entering Foreign Markets: An Econometrics Study of the Markets of A Sample of Arab Countries During the Period (2002-2019)Using Panel Data - Zerkout, Rima; Meskine, Abdelhafid (Milev Journal of Research and Studies, 2021)
The study aims to determine the impact of marketing environment variables on the decision of international companies to choose an FDI strategy from foreign market access strategies,by using cross-sectional data models (panel data) for the period (2002-2019) for a sample of Arab markets. Based on the results of estimating the model, the study concluded that there is a positive correlation between independent variables GNI and the political stability index and the dependent variable FDI flows, and negatively between the population size variable, which means that increasing the population does not necessarily mean attracting foreign direct investment, as for the economic freedom variable It has no effect on foreign direct investment flows to the Arab countries under study.